Pharmacy customers' views towards the potential introduction of pharmacist prescribing: A survey study. - Jan Siefert; Niklas Zimmermann; Kandarp Thakkar; Ágnes Mészáros (PLoS ONE)
Background Pharmacist prescribing has been introduced in several countries owing to systemic issues within healthcare. This systematic change can improve general public's access to prescribed medication. In Germany, pharmacist prescribing and its acceptance among the population remains unexplored because legislators insist on the exclusive right of doctors to prescribe medication. Objectives This study investigated pharmacy customers' views towards pharmacist prescribing. The study sought to determine whether pharmacy customers in Germany could imagine the introduction of pharmacist prescribing. Methods Pharmacy customers in Germany participated in an anonymised survey in August-October 2023. Participants were recruited using a convenience sampling method, mainly from community pharmacies. The questionnaire comprised 28 questions and covers participants' characteristics, key aspects of patient care and statements regarding the topic of pharmacists prescribing. The collected data were coded and analysed using IBM SPSS version 28.0.1. Results In total, 316 participants completed the survey. The average age was 51.0 years, and the majority were females (69.6%, n = 220). Overall, participants reported a high level of satisfaction with the general services provided by community pharmacies. A high to very high level of trust in their community pharmacist (CP) was reported by 84.4% of the participants. A total of 79.1% of the participants stated that pharmacists should be trained for prescribing authorisations. A key finding of this research was that most participants (88.0%), regardless of age and gender, agreed that the concept of pharmacist prescribing is favourable. Conclusion Participants across all age groups were generally positive about pharmacist prescribing and supportive of its implementation, while expressing the need for pharmacists to undergo further training tailored to the specific prescribing authorisation. This study provides groundwork for further research and contributes to policy-making considerations.